An Integrated Approach for the Assessment of Environmental Sustainability in Agro-Industrial Waste Management Practices: The Case of the Tequila Industry - Díaz-Vázquez, Diego; Carrillo-Nieves, Danay; Orozco-Nunnelly, Danielle A.; Senés-Guerrero, Carolina; Gradilla-Hernández, Misael Sebastián (Frontiers in Environmental Science, 2021)
Sustainable waste management is a key component needed to achieve multiple of the Sustainable Development Goals established by the United Nations for the year 2030. Such waste management can reduce the degradation of superficial water sources and can contribute to the sustainable and efficient use of resources. Due to their usually high nutrient and organic loads, agro-industrial wastes pose a threat to soil and water resources and are a major contributor to greenhouse gas generation. In this study, a novel approach was proposed to assess the environmental sustainability of vinasse management practices, integrating an extensive physicochemical characterization of tequila vinasses, a GIS-based weighted overlay analysis and a scenario analysis. Mathematical models were applied for the determination of discharged pollutants (nitrogen, phosphorus, BOD5), as well as greenhouse gas emissions. This methodology was applied to an environmental sustainability assessment of the management practices of tequila vinasses, which are one of the main waste streams generated by the agro-industry in the Mexican state of Jalisco and are one of the main contributors to organic and nutrient loads affecting the water quality of Jalisco’s superficial water sources. Through this integrated approach, critical regions for the management of tequila vinasses were determined and an extensive physicochemical characterization of tequila vinasses was performed and applied to assess the environmental sustainability of four management scenarios for tequila vinasses. These results can be used by decision-makers for the implementation of public policy and infrastructure for the improvement of local and regional waste management systems. Additionally, these data may be used to increase the environmental sustainability of the tequila industry. The proposed methodology has the potential to be applied to different waste-intensive regions as well as different organic waste streams for the assessment of the environmental sustainability of specific management practices considering the local and regional context.